2020
DOI: 10.1093/cercor/bhaa345
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Complexity of the Macro-Scale Neonatal Brain

Abstract: The human adult structural connectome has a rich nodal hierarchy, with highly diverse connectivity patterns aligned to the diverse range of functional specializations in the brain. The emergence of this hierarchical complexity in human development is unknown. Here, we substantiate the hierarchical tiers and hierarchical complexity of brain networks in the newborn period, assess correspondences with hierarchical complexity in adulthood, and investigate the effect of preterm birth, a leading cause of atypical br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…For example, the white matter microstructure, a putative neural basis for information processing speed and intelligence in adults, is present in very early life. 85 Furthermore, distinct hierarchical tiers of network nodes resembling those of the adult brain have been found in neonates, 86 and graph theoretical measures have shown an efficient rich club organization of the neonatal brain structure similar to that observed in adults. 87 …”
Section: Discussionmentioning
confidence: 84%
“…For example, the white matter microstructure, a putative neural basis for information processing speed and intelligence in adults, is present in very early life. 85 Furthermore, distinct hierarchical tiers of network nodes resembling those of the adult brain have been found in neonates, 86 and graph theoretical measures have shown an efficient rich club organization of the neonatal brain structure similar to that observed in adults. 87 …”
Section: Discussionmentioning
confidence: 84%
“…This system is more complex and in turn has a higher hierarchical complexity. Hierarchical complexity is defined as follows, similar to prior studies 25 , 26 . Let G = (V,E) represent a graph with given nodes V = {1,…,n} and edges E = {(i,j) : i,j ∈ V}.…”
Section: Methodsmentioning
confidence: 99%
“…Our results are also consistent with prior evidence that prematurity alters microstructural organisation throughout the cortex: Bouyssi‐Kobar et al (Bouyssi‐Kobar et al, 2018) reported a higher diffusivity in preterm infants in the prefrontal, parietal, motor, somatosensory and visual cortices, and Dimitrova et al (Dimitrova et al, 2021) reported increased cortical tissue water content and reduced neurite density index in posterior cortical regions, and greater cortical thickness in anterior cortex, in preterm compared with term‐born infants. Sensory areas and posterior regions of the cortex have the largest maturational changes in microstructural and morphological profile around birth (Fenchel et al, 2020; Garcia et al, 2018), while the network of cortico‐cortical connections involving sensory‐motor and transmodal integration regions is characterised by a higher complexity in term compared with preterm infants (Blesa et al, 2021). Together with our findings, this suggests that cortical maturation in these regions is vulnerable to the impact of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of the preterm brain at term‐equivalent age has characterised dysmaturation following preterm birth as a global phenomenon (i.e. encompassing the whole brain), with generalised dysconnectivity and atypical topology of developing neural networks, increased water diffusivity, altered white matter microstructure and reduced brain volume and cortical surface area (Batalle et al, 2018; Blesa et al, 2021; Boardman & Counsell, 2020; Telford et al, 2017; Vaher et al, 2022). Motivated by the search for neural antecedents of cognitive impairment observed in some preterm‐born individuals, studies focusing on the neonatal cortex have demonstrated that prematurity impacts cortical growth and microstructural development in a dose‐dependent fashion (Ball, Srinivasan, et al, 2013; Kapellou et al, 2006) and that preterm birth alters cortical folding (Dubois et al, 2019; Neil & Smyser, 2018; Shimony et al, 2016), thalamo‐cortical connectivity (Ball, Boardman, et al, 2013; Boardman et al, 2006) and different regional MRI metrics with varying spatial distribution, including water diffusion measures, markers of myelination and cortical morphology metrics (Ball et al, 2020; Bouyssi‐Kobar et al, 2018; Dimitrova et al, 2021; Ouyang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%